The reflection and re-emission coefficients of hydrogen particles impinging from plasma on the wall in the torsatron Uragan-3M - Bondarenko, V.N.; Petrushenya, A.A. (Вопросы атомной науки и техники, 2017)
The modelling of the radial emissivity profiles of Hα and Hβ lines radiated from hydrogen plasma of the torsatron Uragan-3M in a typical operational regime requires the usage of the programming code KN1D to consider a balance of atom and molecule fluxes on the walls. For this purpose, the reflection and re-emission coefficients were calculated of H atoms and H₂ molecules leaving the plasma and impinging on the plasma-facing surfaces of the stainless steel casings of a helical winding.